Synthesis, Characterization and Antimicrobial Activity Studies of Chlorocobaloximes with Neutral Bases Containing Amine Functionality - Vijaikanth, V.; Vasuki, S.; Immanuel David, C.; Chandana, L.; Sowmya, S.; Murugan, S. (Asian Journal of Chemistry, 2021)
The inorganic cobaloximes of type [Co(Cl)(dmgH)2B]; where dmgH = dimethyl glyoxime and B = neutral bases: glycine, ethyl amine, 2-aminopyridine, 4-aminopyridine, 2,6-diaminopyridine, aniline and 1-napthylamine have been synthesized. The synthesized cobaloximes were characterized by IR, UV-visible, 1H NMR and 13C NMR spectroscopic techniques. The cobaloxime complexes were screened for their antibacterial activity against methicillin resistant Staphylococcus aureus (MRSA) and Acinetobacter baumannii by the zone of inhibition test, biofilm eradication on biomaterial using catheter and modified Congo red agar method. It has been found that the cobaloxime complexes exhibit inhibition against both gram positive and gram negative bacteria and the cobaloximes showed better inhibition towards Gram-negative bacteria compared to Gram-positive bacteria.